Distinct role of primate DLPFC and LIP in hierarchical control of learned saccade sequences - Qingjun Wang; Binchao Shi; Jing Jia; Jingyu Hu; Haoran Li; Xin Jin; Aihua Chen (iScience)
Summary: Learned action sequences are suggested to be organized hierarchically, but how the various hierarchical levels are processed by different cortical regions remains largely unknown. By training monkeys to perform heterogeneous saccade sequences, we investigated the role of the dorsolateral prefrontal cortex (DLPFC) and the lateral intraparietal cortex (LIP) in sequence planning and execution. The electrophysiological recording revealed that sequence-level initiation information was mostly signaled by DLPFC neurons, whereas subsequence-level transition was largely encoded by LIP neurons. Although electrical microstimulation on DLPFC weakly affected sequence performance, inactivating DLPFC significantly increased the initiation latency of the entire sequences, indicating that DLPFC was involved in the sequence initiation. In contrast, either microstimulation or inactivation of area LIP caused improper switches between subsequences, suggesting that LIP played a role in subsequence switch. Overall, these results demonstrated that frontal and parietal cortices play distinct yet complementary roles in controlling learned saccade sequences.